The Effectiveness of Cognitive-Behavioral Hypnotherapy (CBH) on Anxiety and Depression in Military Personnel - Heidarian, Maryam; Afsharinia, Karim; Amiri, Hassan (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The aim of the present study was to evaluate the effectiveness of Cognitive-Behavioral Hypnotherapy (CBH) on anxiety and depression in military personnel. Methods and Materials: This study is applied in terms of its objective and follows a quasi-experimental design with two groups (experimental and control) and a pretest-posttest structure. The statistical population of this study included all military personnel in the city of Kermanshah in 2023–2024. The sampling method was purposive sampling. From the military personnel in Kermanshah, 30 individuals were selected as the sample based on inclusion criteria, including sufficient time to attend therapy sessions, a minimum level of literacy and comprehension to understand the content presented in the sessions, an age range of 20 to 50 years, and the presence of emotional difficulties according to the DASS tests and a semi-structured interview. Exclusion criteria included having chronic disorders, simultaneous participation in other therapeutic sessions for different disorders, absence in more than three sessions during the intervention, and withdrawal from participation. The participants were then divided into two groups of 15 (experimental and control). The data were analyzed using covariance analysis (ANCOVA) with SPSS-26 software. Findings: The results indicated that Cognitive-Behavioral Hypnotherapy (CBH) had a significant effect on anxiety and depression in military personnel at the 0.001 level. Conclusion: Therefore, the findings of the present study can be of interest to military personnel, psychologists, and psychotherapists for reducing anxiety and depression.